LIMITS OF DIRECTOR LIABILITY: BUSINESS JUDGMENT RULES, PIERCING THE CORPORATE VEIL, AND BREACH OF CONTRACT - Kiswah, Maftuha; Ermanto Fahamsyah; Fendi Setyawan (Universitas Bengkulu, 2026)
Limited liability companies inherently separate corporate assets from personal wealth, thereby providing legal protection for their management. However, directors remain strictly bound by fiduciary duties and legal restrictions to ensure the protection of third parties and stakeholders. This article analyzes the legal limits of directors' liability by examining the balance between the Business Judgment Rule (BJR) doctrine, which protects business decisions made in good faith, and the piercing the corporate veil doctrine, which holds directors personally liable for corporate misconduct. Using a normative legal research method with a legal and conceptual approach, this study examines corporate law theories and the latest jurisprudence related to commercial contract violations. The research shows that although the Companies Act protects the BJR, courts have the authority to pierce the corporate veil if a director acts ultra vires, acts in bad faith, or fails to fulfill commercial obligations that result in a breach of contract. Furthermore, the introduction of micro-enterprises with sole directors under the Job Creation Act creates a higher risk of personal liability due to the tendency for asset commingling. The validity of BJR protection requires compliance with procedural safeguards, particularly regarding conflicts of interest. While prior scholarship has examined these doctrines independently, the intersection of BJR protection and veil-piercing liability in commercial contract disputes — particularly following the structural reforms introduced by the Job Creation Act — remains analytically underexplored. This article contributes a systematic normative analysis of how these protective and accountability mechanisms interact, and proposes clearer legal criteria for distinguishing protected business risk from culpable corporate misconduct under Indonesian law. Consequently, corporate management must maintain strict financial separation and transparency to avoid personal legal consequences in commercial disputes.